Rabbani Education for the Development of a Quranic Generation: An Analysis of the Integration of Madrasah-Pesantren Environments - Erikafatul Insani; Nurul Anam (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the role of rabbani education as a pillar of fostering a Qur'anic generation through a case study at MTs. Unggulan Al-Qodiri I Jember. The research method uses a qualitative approach with case studies through observation, interviews, and documentation. Furthermore, the data is analyzed through data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that the integration of madrasah and Islamic boarding school at MTs. Unggulan Al-Qodiri realizes comprehensive rabbani education through a dominant religious curriculum, habituation of daily worship, learning yellow books, strengthening Al-Qur'an recitation, and intensive supervision in the lives of students. The role of teachers as role models, support from the Al-Qur'an Quality Assurance Team (TPMQ), and the OPPM organizational forum further strengthen the internalization of Qur'anic values. Thus, rabbani education within the framework of an integrated madrasah-pesantren becomes a strategic model in producing a Qur'anic generation with strong character and noble morals.